2010
DOI: 10.1007/s00467-009-1377-5
|View full text |Cite
|
Sign up to set email alerts
|

Single infusion of rituximab for persistent steroid-dependent minimal-change nephrotic syndrome after long-term cyclosporine

Abstract: Rituximab (RTX) has been successfully used as a rescue therapy in children with steroid-dependent nephrotic syndrome (SDNS). However, little is known regarding maintenance therapy after a successful response to RTX in such patients. The efficacy and safety of a single RTX infusion (375 mg/m(2)) were assessed in ten patients who had persistent SDNS associated with minimal-change disease (MCD) despite the long-term use of cyclosporine (CsA). The mean follow-up after RTX infusion was 17 months. Applying RTX resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 20 publications
3
57
0
Order By: Relevance
“…While the underlying pathophysiology is still being actively investigated, T-cell dysfunction and various permeability factors have been implicated in the pathogenesis [78], [79] and [80]. RTX has been used with some success in children with steroid-dependent idiopathic nephrotic syndrome, as shown in several case reports [81], [82], [83] and [84]. A randomized clinical trial of 54 children with steroid-and calcineurin inhibitordependent nephrotic syndrome treated with RTX versus standard therapy showed that proteinuria decreased by 70% more in the RTX arm [85].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…While the underlying pathophysiology is still being actively investigated, T-cell dysfunction and various permeability factors have been implicated in the pathogenesis [78], [79] and [80]. RTX has been used with some success in children with steroid-dependent idiopathic nephrotic syndrome, as shown in several case reports [81], [82], [83] and [84]. A randomized clinical trial of 54 children with steroid-and calcineurin inhibitordependent nephrotic syndrome treated with RTX versus standard therapy showed that proteinuria decreased by 70% more in the RTX arm [85].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…There have been many reports recently of the steroid-sparing effect of RTX in NS [4][5][6][7][8], suggesting that not only T cells but also B cells may play a role in the pathogenesis of NS. The mechanism of RTX action in NS treatment is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a single infusion of RTX can delete B cells for only about 5 months [4][5][6][7][8]. Thus, the establishment of a proper treatment protocol, such as the number of RTX infusions, timing of the introduction of RTX, and how to taper the PSL dose, is desired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations